2021
DOI: 10.1002/qre.2950
|View full text |Cite
|
Sign up to set email alerts
|

The impracticality of homogeneously weighted moving average and progressive mean control chart approaches

Abstract: There is growing literature on new versions of “memory‐type” control charts, where deceptively good zero‐state average run‐length (ARL) performance is misleading. Using steady‐state run‐length analysis in combination with the conditional expected delay (CED) metric, we show that the increasingly discussed progressive mean (PM) and homogeneously weighted moving average (HWMA) control charts should not be used in practice. Previously reported performance of methods based on these two approaches is misleading, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 82 publications
(129 reference statements)
1
38
0
Order By: Relevance
“…From Figure 6, it can be observed that for small 𝜆 the proposed MTEWMA scheme performs better under the time-varying case compared to the asymptotic one in terms of the ARL profile. This confirms the findings of Knoth et al 26 reporting the worst performance of the TEWMA scheme and other memory-type schemes with asymptotic control limits. For large 𝜆 values, the MTEWMA scheme performs similarly for both cases.…”
Section: Time Varying Versus Asymptotic Performancesupporting
confidence: 91%
“…From Figure 6, it can be observed that for small 𝜆 the proposed MTEWMA scheme performs better under the time-varying case compared to the asymptotic one in terms of the ARL profile. This confirms the findings of Knoth et al 26 reporting the worst performance of the TEWMA scheme and other memory-type schemes with asymptotic control limits. For large 𝜆 values, the MTEWMA scheme performs similarly for both cases.…”
Section: Time Varying Versus Asymptotic Performancesupporting
confidence: 91%
“…Knoth et al 13 . were the first to mention a decline in the performance of PM chart through their CED curves, which can be confirmed from the conditional steady state ARL values of PM chart in Tables 2 and 3.…”
Section: Criticism On Pm Chartmentioning
confidence: 65%
“…Here, constant q$q$ becomes the sensitivity parameter of PM control chart that is, a smaller value of q$q$ (i.e., close to 0) increases the sensitivity of PM chart and creates inertia problem at the same time, whereas a larger value of q$q$ can reduce the severity of inertia problem at the cost of lower sensitivity. Knoth et al 13 . also pointed out the deficiency of PM control chart in monitoring the processes where shift does not occur at the start of monitoring.…”
Section: Criticism On Pm Chartmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the recently proposed methods, such as the triple multivariate exponentially weighted moving average chart of Malela-Majika et al, 2 lead to weighting patterns that violate this basic requirement. For many other examples, see Mahmoud and Woodall 3 and Knoth et al 4,5 The homogeneously weighted moving average (HWMA) chart of Abbas 6 gives a specified weight to the current data point and distributes equal weights to all past data values. Knoth et al 5 showed that this approach has poor performance even though the weight pattern restriction of Lai 1 is typically met after the first few observations.Methods should be compared based on steady-state average run length (ARL) performance, where it is assumed that any process shift is delayed.…”
mentioning
confidence: 99%